Soluble Human Angiotensin- Converting Enzyme 2 as a Potential Therapeutic Tool for COVID-19 is Produced at High Levels In Nicotiana benthamiana Plant With Potent Anti-SARS-CoV-2 Activity - Mamedov, Tarlan; Gurbuzaslan, Irem; Yuksel, Damla; Ilgin, Merve; Mammadova, Gunay; Ozkul, Aykut; Hasanova, Gulnara (Frontiers in Plant Science, 2021)
The COVID-19 pandemic, which is caused by SARS-CoV-2 has rapidly spread to more than 222 countries and has put global public health at high risk. The world urgently needs a safe, cost-effective SARS-CoV-2 coronavirus vaccine as well as therapeutic and antiviral drugs to combat COVID-19. Angiotensin-converting enzyme 2 (ACE2), as a key receptor for SARS-CoV-2 infections, has been proposed as a potential therapeutic tool in COVID-19 patients. In this study, we report a high level production (about ~0.75 g /kg leaf biomass) of human soluble (truncated) ACE2 in the Nicotiana benthamiana plant. After the Ni-NTA single-step, the purification yields of recombinant plant produced ACE2 protein in glycosylated and deglycosylated forms calculated as ~0.4 and 0.5 g/kg leaf biomass, respectively. The plant produced recombinant human soluble ACE2s successfully bind to the SARS-CoV-2 spike protein. Importantly, both deglycosylated and glycosylated forms of ACE2 are stable at elevated temperatures for extended periods of time and demonstrated strong anti-SARS-CoV-2 activities in vitro. The IC50 values of glycosylated and deglycosylated ACE2 were ~1.0 and 8.48 μg/ml, respectively, for the pre-entry infection, when incubated with 100TCID50 of SARS-CoV-2. Therefore, plant produced soluble ACE2s are promising cost-effective and safe candidates as a potential therapeutic tool in the treatment of COVID-19 patients.